Повороти долі фотографа А.М. Павловича та Полтавський музей - Сулима, О.С. (Сіверщина в історії України, 2020)
У статті проаналізована тематична складова фотографічної
колекції Полтавського краєзнавчого музею імені Василя Кричевського – світлини уродженця Полтави, фотомитця Анатолія Миколайовича Павлóвича (1880–19?). Висвітлена взаємодія фотографа з
Природничо-історичним музеєм Полтавського губернського земства
під час його відрядження до Полтавської губернії у 1907–1908 рр.
Зокрема, ним були виготовлені на замовлення полтавських музейників копії гравюр Х.Г.Г. Гейслера до праць дослідника П.С. Палласа, що зберігалися у Чернігівському музеї. Також подаються короткі
відомості про поштові картки Общини Святої Євгенії, ілюстровані видами Полтави, видрукувані за світлинами Анатолія Миколайовича. Введено до наукового обігу невідомі фотодокументи, виготовлені А.М. Павлóвичем, – стереопари з видами Криму 1912 р. Thematic part of the Vasyl Krychevsky Poltava Local Lore Museum
photographic collection – photos of Poltava citizens, photo of artist
A.M. Pavlovych (1880–19?) – is analyzed in the article. He studied
photographic art in Saint Petersburg, where he cooperated with Ethnographic
department of the Emperor Alexander III Russian Museum
and Petersburg Care Committee of sisters of Red Cross (St. Yevheniia
Society) Publish house. Anatolii Mykolaievych had a business trip
to Chernihiv and Poltava Huberniias on the instruction of the Russian
Museum in 1907-1908. In this particular time the photographer cooperated
with the Natural History Museum of Poltava Huberniia Zemstvo.
For example, he made copies of Kh.H.H. Heisler’s engravings for works
of explorer P.S. Pallas from the V.V. Tarnovskyi Chernihiv Museum by
order of Poltava museum workers. Brief information about postcards
of St. Yevheniia Society, illustrated with Poltava sites, printed according
to photos of A.M. Pavlovych. He had “a great voyage” at the Russian
Empire territory, including Crimea Peninsula, by order of Head of
St. Yevheniia Society Publish house N.N. Cherniahin in 1912. The result
of the voyage, except for numerous picture postcards published by
St. Yevheniia Society later, included stereopairs with images of Crimea
with local sightseeing and landscapes.
Thereby information about the Vasyl Krychevsky Poltava Local Lore
Museum photographic collection forming at the early 20th century is added.
Data concerning photo artist A.M. Pavlovych, who became popular
outside of his Motherland, though belonged to historic figures important
for Poltava and its outskirts in the Modern Epoch, are systematized.